Influence of virtual changes in buildingconfigurations of a real street canyon on thedispersion of PM10 - Garcia, João (2018)
Four geometrical configurations of a real street canyon in Barreirocity (Portugal) are considered to study their influence on the dis-persion of PM10. These configurations include actual architectural layout of the street (Option 1), and three virtual cases (Options1–3). Option 2 includes the modification of real geometry byincluding 4 m gaps between the buildings situated on the southern part of the street canyon. Option 3 considers 6 m gaps betweenbuildings as opposed to 4 m gaps in Option 2. Option 4 assumesthe same height for all buildings on the southern part of the street canyon, with no gaps between buildings. Computational fluid dynamics code (CFD), FLUENT, is used to simulate the detailed flow and turbulence characteristics in three-dimensional domain ofchosen street canyon, together with the PM10 dispersion for both the summer and winter seasons. The modelled PM10 concentra-tions were then compared with the measured data at seven differ-ent locations in the street canyon. Our results indicate up to 23%lower PM10concentrations at 1.5 m above the road level during the along-canyon wind direction due to the channelling of flow,compared with those observed during the cross-canyon wind direction. Detailed inspection of the results obtained from the Options 1–3 indicated that the spacing between the buildings tendto increase particle dilution during the cross-canyon winds resulting in up to 20, and 22% reduced concentrations for options 2,and 3 respectively, compared with the actual configuration (Option1). The largest improvement ( 7%) in the PM10concentrations wasgiven by Option 2, while other options showed modest changes.Possible reasons for these changes under varying meteorological conditions are explained in the context of changing building con-figurations and their implications in city planning.